2009
DOI: 10.1016/j.iilr.2009.07.001
|View full text |Cite
|
Sign up to set email alerts
|

LIS community's perceptions towards open source software adoption in libraries

Abstract: The purpose of the study was to investigate LIS Community's perceptions towards Open Source Software (OSS) adoption in libraries. The study adopted quantitative research design and a Likert type scale of 20 items was designed to collect data. Attention was given to three variables e organization type (public/private sector), library type (academic/ public/special), and country type (developed/developing). A total of 370 responses were received from 48 countries. Collected data were analyzed using descriptive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 7 publications
2
28
0
Order By: Relevance
“…Similar indications in the ILMS sector are evident and studies indicate strong positive perception and inclination toward adoption of OSS (Rafiq, 2009). The study of Kiriyanant (2012) …”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…Similar indications in the ILMS sector are evident and studies indicate strong positive perception and inclination toward adoption of OSS (Rafiq, 2009). The study of Kiriyanant (2012) …”
Section: Resultssupporting
confidence: 59%
“…Poulter (2010) observed that OSS aids libraries and had great potential but was hobbled by its intrinsically technical appeal. An international study on perceptions on adoption of OSS in libraries indicated a very positive response and further found that developing countries indicated higher interests in OSS solutions when compared to developed countries (Rafiq, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Chudnov, 1999, Jaffe and Careaga, 2007, Rhyno, 2008Krishnamurthy, 2008 ;Rafiq, 2009), and writers such as Bissels, (2008), Caldwell (2007), Chad (2007) (Jaffe & Careaga, 2007). Hoy and Koopman (2008) argued that, due to the risk averse nature of libraries, many only consider OSS for non-critical services, and that the parent institution's information technology infrastructure may dictate what library software can be used, with the academic environment being notoriously conservative in this respect.…”
Section: Open Source Library Management Systemsmentioning
confidence: 99%
“…The synergy between the open source movement and libraries is a recurring theme in the literature (Chudnov, 1999;Jaffe and Careaga, 2007;Rhyno, 2008;Krishnamurthy, 2008;Rafiq, 2009), and writers such as Bissels (2008), Caldwell (2007), Chad (2007) and Tedd (2007) agree that open source LMSs are now a viable solution. Despite this, evidence suggests libraries have been slow to adopt OSS (open source software), particularly in the UK.…”
Section: Open Source Lmssmentioning
confidence: 99%
See 1 more Smart Citation